Behaviour of kenaf fiber reinforced concrete - Mohd Zuraidi, Salehudin (2013)
Hibiscus cannabinus L as known as kenaf is one of the natural fibers that having many advantages such as lightweight, no corrosion and low cost as alternative reinforcement for reinforced concrete beam. The using of natural fiber in construction fields will improve the promotion of green building materials kenaf fiber is as an alternative to use in concrete structure. The purpose of this research is to study the kenaf fiber of reinforced concrete beam in term of flexural and compression strength with main bar and without main bar added with kenaf fibers. Other than that, this research is to study the effect of amount of kenaf fibers added to the concrete in term of strength, cracking pattern and deflection. The compressive strength test was conducted on the different type of concrete mix. This study was implemented to do the comparison between a normal concrete to the different amount of kenaf fibers. A 3 point bending test also was conducted for beam with main bar and without main bar to determine the flexural strength, deflection and crack pattern. From the flexural test result the beam contain 30kg/m3 give the close result to control beam. As conclusion, the amount of kenaf below than 30kg/m3 can give some improvement on flexural strength of reinforced concrete beam.